Comparison of clinical characteristics of coronavirus disease (COVID-19) and severe acute respiratory syndrome (SARS) as experienced in Taiwan. Issue 36 (July 2020) - Su, Yu-Jang; Lai, Yen-Chun
Highlights: From our data, we know 2019-nCoV invades more common in male, not likely the SARS that is female predominant. The 2019-nCoV patients are around 20 years older than the population of SARS. Young adults are susceptible to SARS than the children and elderly. Hypoalbuminemia are noted in SARS patients, it needs a longer time to study whether the 2019-nCoV possesses the same presentation.